An optimal transmit-receive rate tradeoff in Gray-Wyner network and its relation to common information - Viswanatha, K.; Akyol, E.; Rose, K. (2011 IEEE Information Theory Workshop, 2011)
This paper considers the problem of characterizing the optimal tradeoff between the total transmit versus receive rate in the Gray-Wyner network. This tradeoff plays a crucial role in many important practical applications including establishing fundamental limits in databases for correlated sources and in minimum cost routing for networks. We develop the insight into this tradeoff by defining two quantities C(X, Y; R' ) and K(X,Y;R"), which quantify the shared rate as a function of the total transmit and receive rates respectively. Closely tied up with this tradeoff is the notion of common information of two dependent random variables. The two most influential definitions are due to Wyner [2] and Gács-Körner [1]. Though it is well know that these definitions can be characterized as two extreme points in the Gray-Wyner region, no contour with operational significance is known which connects them. We will show that the tradeoff between transmit and receive rates leads to a contour of points on the boundary of Gray-Wyner region which passes through the operating points of Wyner and Gács-Körner. We use these properties to derive alternate characterizations for the two definitions of common information under a broader unified framework.